World book 2001 (World Book, 2000)
Contains every article from The World Book Encyclopedia plus thousands more, extensive multimedia including videos, maps, 360-degree panoramas, photographs, sound, animations and simulations, World Book Dictionary, Research Wizards, "Surf the Millennium" on simulated Web sites for each century, one-year subscription to World Book Online (internet access required), online encyclopedia updates (internet access required).